2020
DOI: 10.1002/bjs.11487
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive oesophagectomy with extended lymph node dissection and thoracic duct resection for early-stage oesophageal squamous cell carcinoma

Abstract: Background: Oesophageal squamous cell carcinoma is an aggressive disease owing to early and widespread lymph node metastases. Multimodal therapy and radical surgery may improve prognosis. Few studies have investigated the efficacy of radical lymph node and thoracic duct resection. Methods: Patients with oesophageal squamous cell carcinoma who underwent transthoracic minimally invasive oesophagectomy (TMIE) for cancer at Keio University Hospital betweenJanuary 2004 and December 2016 were selected. Between 2004 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 30 publications
3
17
0
Order By: Relevance
“…Especially in terms of the definition of TDLN-Ut, dissecting the plane including the sympathetic nerve, the left pleura and the aortic arch are identified in the upper mediastinum in the dorsal mobilization of the esophagus as introduced in the surgical procedure in a previous report. 11 Therefore, the TD and all the surrounding lymphatic/connective tissues are to be mobilized together. The plane, which included the sympathetic nerve behind the left recurrent laryngeal nerve, TD, and other lymphatic/connective tissues, were dissected after the lymphadenectomy surrounding left recurrent laryngeal nerve was done.…”
Section: Surgical Procedure Ln Station Numbers and Surgical Outcomesmentioning
confidence: 99%
“…Especially in terms of the definition of TDLN-Ut, dissecting the plane including the sympathetic nerve, the left pleura and the aortic arch are identified in the upper mediastinum in the dorsal mobilization of the esophagus as introduced in the surgical procedure in a previous report. 11 Therefore, the TD and all the surrounding lymphatic/connective tissues are to be mobilized together. The plane, which included the sympathetic nerve behind the left recurrent laryngeal nerve, TD, and other lymphatic/connective tissues, were dissected after the lymphadenectomy surrounding left recurrent laryngeal nerve was done.…”
Section: Surgical Procedure Ln Station Numbers and Surgical Outcomesmentioning
confidence: 99%
“…Tao (23) reported that PLG is a safe and effective method to reduce post-operative chylothorax. Both Satoru (22) and Matsuda (17) concluded that ligation has a superior effect on long-term prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…The majority (85.7%) of patients who aspirated thickened liquids showed silent aspiration without a cough re ex, that is, categorized into PAS 8. The time to start oral intake, the time to nish diet modi cation (i.e., acquisition of regular food), and the date of discharge were POD 13 (IQR, 9-18), 20 (IQR, [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29], and 26 (IQR, 21-40), respectively, signi cantly longer in the NOI group than in the OI group (p<0.001). On the other hand, the incidence of oral intake-related complication (i.e., aspiration pneumonia) was not signi cantly different between the NOI and OI groups from the initiation of oral intake until the time of discharge (10.9% vs. 5.7%, p=0.226).…”
Section: Swallowing Function and Oral Intake Statusmentioning
confidence: 99%